Stefan Problem with Change Density Upon Change of Phase (I) (Journal of Partial Differential Equations, 2020)
In this paper, we establish the existence of one-dimensional classical solution of one-phase problem and its continuous dependence. In addition, we prove that if &#949 &#8594 0, the free boundary X(t) withdraws and solution converges to the solution of classical Stefan problem. The two-phase problem wiU be discussed in the coming paper.
Keywords: asymptotic behavior; existence; phase transition problem